2013
DOI: 10.1111/dmcn.12096
|View full text |Cite
|
Sign up to set email alerts
|

Good outcome in patients with early dietary treatment of GLUT‐1 deficiency syndrome: results from a retrospective Norwegian study

Abstract: Aim The aim of this study was to characterize patients diagnosed with glucose transporter protein‐1 deficiency syndrome (GLUT‐1 DS) clinically and genetically, and to evaluate the effect of treatment with the classic ketogenic or modified Atkins diet. Method We retrospectively studied medical records of 10 patients diagnosed with GLUT‐1 DS. Four females and six males with a median age of 15 years were included. Results The study illustrates the genetic and clinical heterogeneity of GLUT‐1 DS. Analysis of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 35 publications
4
55
0
4
Order By: Relevance
“…To date, about 200 patients have been identified in the world mainly in the United States and Europe [17]. The Norway National Registry indicates a point prevalence of 2.6 per 1 million inhabitants [18]. In Italy, a national registry of GLUT1 DS is not yet available and the prevalence cannot be estimated.…”
Section: Methodsmentioning
confidence: 99%
“…To date, about 200 patients have been identified in the world mainly in the United States and Europe [17]. The Norway National Registry indicates a point prevalence of 2.6 per 1 million inhabitants [18]. In Italy, a national registry of GLUT1 DS is not yet available and the prevalence cannot be estimated.…”
Section: Methodsmentioning
confidence: 99%
“…The ketogenic diet is the standard treatment for glucose transporter type 1 (GLUT1) deficiency, a rare genetic condition caused by impaired glucose transport into the brain and associated with an abnormality in the gene SLC2A1 (De Vivo et al, 1991). Studies have shown up to 90% of patients with seizure freedom on the ketogenic diet or modified Atkins diet, including adults (Cervenka et al, 2017a, Ramm-Pettersen et al, 2013). Similarly, for patients with pyruvate dehydrogenase deficiency, where the diet overcomes the deficiencies in the catalytic component of the mitochondrial enzyme pyruvate dehydrogenase complex by providing an alternative source of acetyl coenzyme A, the ketogenic diet is considered first-line therapy and should be implemented as soon as the patient is identified (Kass et al, 2016, Klepper and Leiendecker, 2007, Pong et al, 2012).…”
Section: Efficacy and Indications In Adultsmentioning
confidence: 99%
“…Total IQ improvement was found in 1/13 patients in an Italian group (De Giorgis et al., ) and in 4/6 patients in a Japanese population (Ito et al., ). Younger patients demonstrated the most noteworthy response on KD (Ramm‐Pettersen et al., ).…”
Section: Introductionmentioning
confidence: 99%